2002
DOI: 10.1074/jbc.m110333200
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 and MD-2 Expression Is Regulated by Immune-mediated Signals in Human Intestinal Epithelial Cells

Abstract: The intestinal epithelium is continually exposed to a high intraluminal concentration of diverse bacteria and bacterial products (1, 2). Despite the density of commensal bacteria and their products, the intestinal mucosa maintains a controlled state of inflammation. By contrast, invasive or toxin-producing pathogenic bacteria elicit acute inflammation and secretion of pro-inflammatory cytokines by intestinal epithelial cells and lamina propria mononuclear cells (3, 4). Idiopathic inflammatory bowel disease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
256
4
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 333 publications
(273 citation statements)
references
References 66 publications
(67 reference statements)
11
256
4
2
Order By: Relevance
“…Tollip is a Toll/ IL-1R (TIR) domain-containing inhibitory protein that is bound to IRAK (21). We have shown that Tollip expression is high in intestinal epithelial cells that are poorly responsive to LPS (22). Furthermore, Tollip expression increases in LPS-or LTA-treated intestinal epithelial cells and is associated with hyporesponsiveness to PAMPs (9).…”
Section: Expression Of Inhibitors Of Tlr Signalingmentioning
confidence: 83%
“…Tollip is a Toll/ IL-1R (TIR) domain-containing inhibitory protein that is bound to IRAK (21). We have shown that Tollip expression is high in intestinal epithelial cells that are poorly responsive to LPS (22). Furthermore, Tollip expression increases in LPS-or LTA-treated intestinal epithelial cells and is associated with hyporesponsiveness to PAMPs (9).…”
Section: Expression Of Inhibitors Of Tlr Signalingmentioning
confidence: 83%
“…27 The effect of IFN-␣ on TLR4 is unique; other cytokines like TNF-␣ or IFN-␥ lead to little or no TLR4 increase. 28 Although binding of lipopolysaccharide to TLR4 usually results in receptor downregulation, causing endotoxin tolerance, 25 IFN-␣ was capable of counteracting this inhibitory effect. Thus, simultaneous signaling of TLR9, triggering IFN-␣ production, and TLR4, inducing cytokine production, is required for a sustained immune response to TLR4 ligands.…”
Section: Discussionmentioning
confidence: 99%
“…TLRs are expressed by most immune cells including PMN as well as epithelial cells. While recent studies have uncovered a number of different TLRs, a majority of the research has focused on TLR4 which was the first of these receptors to be discovered, and to a lesser extent TLR2 , Abreu et al 2002, Hausmann et al 2002, Lorenz et al 2002, Backhed & Hornef 2003, Fan & Malik 2003. Discovery of a naturally occurring mutation in mice for the TLR4 gene (Takeda et al 2003) was central to our understanding of the importance of TLRs.…”
Section: Microbial-derived Products and The Inflammatory Responsementioning
confidence: 99%
“…In humans, a number of alleles of TLR4 have been identified and are associated with an increased risk of septic shock (Fenton & Golenbock 1998, Abreu et al 2002, Hausmann et al 2002, Lorenz et al 2002, Backhed & Hornef 2003, Fan & Malik 2003, Sabroe et al 2003. Although TLR4 has been shown to interact with heat shock proteins and taxol, arguably the most important role for TLR4 is as a cellular receptor for bacterial LPS, a central bacterial cell wall component comprising ~13% of the gram negative envelope (Fenton & Golenbock 1998, Viriyakosol et al 2000, Abreu et al 2002, Hausmann et al 2002, Lorenz et al 2002, Backhed & Hornef 2003, Fan & Malik 2003.…”
Section: Microbial-derived Products and The Inflammatory Responsementioning
confidence: 99%